Genius Camp - Grabenstein, Chris (Grabenstein, Chris. Smartest kid in the universe (Series), 2021)
"Twelve-year-old Jake McQuade-the smartest kid in the universe-goes to a camp for geniuses, where he goes up against the Virtuoso quantum computer, the smartest machine in the universe"--